Types and Density of Aquatic Plant in Rengas Lake, Buluh Cina Village, Siak Hulu Sub-Regency, Kampar Regency, Province of Riau. - Fazli, Muhammad; ', Efawani; ', Yuliati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This Research aims to discover the types and density of aquatic plant in RengasLake, Buluh Cina Village, Siak Hulu Sub-regency, Kampar Regency, Province of Riau.This research was conducted on January until April 2013. This research uses SurveyMethod with doing both observing and sampling. Samples were taken 3 times, once aweek and they were analyzed in the Picology Laboratory of the Fisheries and MarineScience Faculty, University of Riau.Result shown that there are 3 classes, 6 families and 6 species of aquatic plants.There are Eicchornia crassipes, Vetiveria zizaniodes, Salvinia natans, Ipomoeaaquatica, Myriophyllum brasilliense, and Cyperus esculentus. From those aquaticplants, the species that has the most value of density is Eucchornia crassipes (54 - 82cells/m2) and the least value of density is Myriophyllum brasilliense (20-66cells/m2)Based on data obatained, Eucchornia crassipes is relatively the most denseaquatic plant (16 - 28%) and Myriophyluum brasillense is the least (7-19%).Keyword: Aquatic Plant, Density, Rengas Lake